2017
DOI: 10.3892/ol.2017.5870
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-548c-3p inhibits T98G glioma cell proliferation and migration by downregulating c-Myb

Abstract: Abstract. MicroRNAs (miRNAs/miRs) are short non-coding RNAs (between 20 and 22 nucleotides) that regulate gene expression by binding to the 3'-untranslated region of target mRNA, and preventing protein translation or inducing mRNA destabilization. miRNAs are predicted to target ~60% of all mRNAs, therefore providing a marked degree of regulation of a number of cellular processes. In the present study, the expression of miR-548c-3p was determined by reverse transcription-quantitative polymerase chain reaction a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…The mature miR-548c-3p is obtained from miR-548c and consists of 22 nucleotides. A mass of studies have indicated that miR-548c-3p is involved in various cancers, including prostate cancer,23 glioma,24 gastric cancer,25 and BC 26. Nevertheless, the underlying molecular mechanisms of miR-548c-3p in BC remains undiscovered.…”
Section: Introductionmentioning
confidence: 99%
“…The mature miR-548c-3p is obtained from miR-548c and consists of 22 nucleotides. A mass of studies have indicated that miR-548c-3p is involved in various cancers, including prostate cancer,23 glioma,24 gastric cancer,25 and BC 26. Nevertheless, the underlying molecular mechanisms of miR-548c-3p in BC remains undiscovered.…”
Section: Introductionmentioning
confidence: 99%
“…Glioma, a tumor in the central nervous system, has a poor survival rate and high mortality (Zhang Y. et al, 2017 ). The latest report suggested that the incidence of glioma has increased from 5.9/100,000 people to 6.61/100,000 people between 1973 and 2016 with the application of improved radiological diagnosis (Lu et al, 2017 ). Despite multiple treatment options, cancer remains one of the leading causes of death worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, this study also found that dysregulated hsa_circ_0005927 was related to the tumor size, suggesting that the expression of hsa_circ_0005927 may be related to the growth and proliferation of LCXW. What is more, the downregulated of predicted miRNA of hsa_circ_0005927 is also associated with progression of some tumors 22‐25,31 . It is worth noting that predicted miR‐592 function as a tumor suppressor in NSCLC by targeting SOX9 , 25 SOX9 is significantly upregulated in NSCLC and NSCLC cell lines 32 and promote the proliferation of lung cancer cells, 33 and SOX9 also mediates Notch1‐induced epithelial mesenchymal transformations (EMT) in lung adenocarcinoma 34 .…”
Section: Discussionmentioning
confidence: 99%